2003
DOI: 10.1515/jpm.2003.026
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for antenatal surveillance of high-risk pregnancies with ambulatory and home fetal heart rate monitoring – an update

Abstract: Antepartum fetal surveillance is routinely used to assess the risk of fetal death in high-risk pregnancies. Traditionally, testing is performed in the hospital or outpatient clinic by trained medical staff. New equipment is now available that is easy to operate and can be used for self-monitoring of the fetal heart rate (FHR) in the home setting. The tracings are transmitted by modem to a referral center for immediate interpretation by a health provider. The aim of this review was to assess the current data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Careful review of the literature revealed that there are no end-point negative outcomes for low-risk obstetrical patients who receive fewer than the traditionally accepted number of face-toface encounters with their provider (Alexander & Kotelchuck, 2001;Dowswell et al, 2010;McDuffi e, Beck, Bischoff, Cross, & Orleans, 1996;McDuffi e, Bischoff, Beck, & Orleans, 1997;Public Health Service Expert Panel on Pernatal Care, 1989;Villar, Carroli, Khan-Neelofur, Piaggio, & Gülmezoglu, 2001;Walker, McCully, & Vest, 2001). Further, studies have demonstrated safety and effi cacy of home-based and telemedicine-mediated monitoring of high-risk pregnancies (Hod & Kerner, 2003), high obstetric patient and provider satisfaction in postdischarge support provided via videoconference (Lindberg, Christensson, & Ohrling, 2009;Lindberg, Ohrling, & Christensson, 2007), and use of telemedicine for a wide variety of obstetric uses, such as reading ultrasounds, managing diabetes, and providing postpartum support to parents and children (Magann et al, 2011). However, we did not fi nd a single program using telemedicine to provide routine monitoring of low-risk pregnancies in our review of the literature.…”
Section: Program Developmentmentioning
confidence: 99%
“…Careful review of the literature revealed that there are no end-point negative outcomes for low-risk obstetrical patients who receive fewer than the traditionally accepted number of face-toface encounters with their provider (Alexander & Kotelchuck, 2001;Dowswell et al, 2010;McDuffi e, Beck, Bischoff, Cross, & Orleans, 1996;McDuffi e, Bischoff, Beck, & Orleans, 1997;Public Health Service Expert Panel on Pernatal Care, 1989;Villar, Carroli, Khan-Neelofur, Piaggio, & Gülmezoglu, 2001;Walker, McCully, & Vest, 2001). Further, studies have demonstrated safety and effi cacy of home-based and telemedicine-mediated monitoring of high-risk pregnancies (Hod & Kerner, 2003), high obstetric patient and provider satisfaction in postdischarge support provided via videoconference (Lindberg, Christensson, & Ohrling, 2009;Lindberg, Ohrling, & Christensson, 2007), and use of telemedicine for a wide variety of obstetric uses, such as reading ultrasounds, managing diabetes, and providing postpartum support to parents and children (Magann et al, 2011). However, we did not fi nd a single program using telemedicine to provide routine monitoring of low-risk pregnancies in our review of the literature.…”
Section: Program Developmentmentioning
confidence: 99%
“…Telemonitoring has also been shown to be more cost effective than traditional patient physician interaction in high-risk pregnancies [17]. Consequently, a variety of e-health tools have been developed, ranging from smart wearable sensors for fetal electrocardiography [18] [19], over health platforms for nutrition and lifestyle in pregnancy [20] to pregnancy-specific smartphone applications [21]. Positive attitudes of pregnant women towards the use of apps in pregnancy monitoring along with improvements in patient empowerment have been proven [22].…”
Section: Telemedicine In Obstetricsmentioning
confidence: 99%
“…Studies on and experience with the use of mobile CTG devices used for telemedical home monitoring have consistently shown that the technique is safe and use of mobile CTG devices is associated with high patient satisfaction. The introduction of electronic documentation systems is generally recommended (online assessment with a high degree of reproducibility) (EL IV [35,42,76]). But all systems which interfere with the physicianʼs ultimate authority to take decisions and decide on the appropriate therapy and which would have consequences in terms of the physicianʼs liability for damages should be firmly rejected.…”
Section: Other Approachesmentioning
confidence: 99%